Classical Tradition of Social Theory - Chapagai, Shreejana (Rural Development Journal, 2017)
This paper based on classical social theories, to study of conceptual from in a society. The idea of science and society are discussed in this paper. The comet's views scientific vision of sociology and heavenly vision of sociology. In a society, classical theories are Karl Marx, Emile Durkheim and Max Weber’s. Karl Marx emphases, revolutionary science and Das capital. The logic of social revolutions. Emile Durkheim to focus on promise of sociology which describe liberal vision of history and modernity. His great theory to discuss suicide in community. It deals with science, truth and moral hope. Another theory Max Weber which deals against the Marx and discussion the bureaucratic system in a society. He explaining western modernity and the irony of history and charisma with bureaucracy the modern dream turned nightmare.